Mechanistic insights into NFIX frameshift mutations in Malan syndrome: proteasomal degradation-mediated haploinsufficiency - Zhou, Yan; Zou, Linbing; Li, Yaoyao (Frontiers in Genetics, 2025)
ObjectiveTo investigated the pathogenic mechanism of NFIX frameshift mutations in Malan syndrome.MethodsReviewed the clinical diagnosis and treatment processes of the Malan syndrome proband, analyzing the relationship between NFIX frameshift mutation genotypes and clinical phenotypes, and the inheritance pattern. To analyzed the functional domain where the mutation was located and the conservation of the mutated amino acid residue, thereby elucidating the potential impact of the mutation on the protein. Validated effects on pre-mRNA splicing using RDDCSC, SpliceAI, and FF databases. Assessed variant pathogenicity via MutationTaster, PolyPhen-2, and VarCards. Constructed wild-type/mutant plasmids, transfected to HEK293T cells, and quantified NFIX mRNA and protein expression levels via qPCR and Western blot. Analyzed degradation pathways using ubiquitin-proteasome inhibitor MG132 and autophagy-lysosome inhibitor Chloroquine (CQ).ResultsThe proband exhibited intellectual disability, distinctive facial features, ocular abnormalities, scoliosis, and primary infertility. A de novo mutation in NFIX (c.164delC, p.Ala55Glyfs*2) associated with these phenotypes was identified. Neither the proband’s father nor his mother was found to have this mutation. Parental testing confirmed de novo inheritance. The amino acid at position 55 was highly conserved and had been Alanine in 5 species. Results from databases including RDDCSC, SpliceAI, and FF indicated that the NFIX c.164delC p.Ala55Glyfs*2 mutation did not affect splicing function. Predictions by MutationTaster and PolyPhen-2 classified the c.707G>A p.Arg236Gln mutation as “damaging,” suggesting an altered amino acid sequence, frameshift mutation, NMD, and potential modification of protein characteristics. Quantitative real-time PCR (qPCR) analysis detected comparable mRNA levels between mutant and wild-type strains. In contrast, Western blotting revealed significantly diminished protein expression in the mutant (P < 0.05), suggesting post-transcriptional regulation effects. Results from protein degradation pathway analysis demonstrated that the truncated protein generated after mutation was degraded via the ubiquitin-proteasome pathway.ConclusionThe NFIX c.164delC p.Ala55Glyfs*2 frameshift mutation did not significantly affect mRNA expression levels, but induced protein degradation via the ubiquitin-proteasome pathway, resulting in haploinsufficiency and ultimately causing Malan syndrome.